Aberrant Cerebello-Thalamo-Cortical Functional and Effective Connectivity in First-Episode Schizophrenia With Auditory Verbal Hallucinations. (27th August 2022) - Wei, Yarui; Xue, Kangkang; Yang, Meng; Wang, Huan; Chen, Jingli; Han, Shaoqiang; Wang, Xiaoxiao; Li, Hong; Zhang, Yong; Song, Xueqin; Cheng, Jingliang
Abstract: The thalamus is known to be impaired in schizophrenia patients with auditory verbal hallucinations (AVHs). Abnormal filtering function of the thalamus has been found in schizophrenia patients with AVHs. However, a whole-structure approach has commonly been adopted when investigating thalamic dysconnectivity in patients with AVHs, and it remains unclear which thalamic nucleus is the critical structure underlying AVHs. Here, we investigated voxel-wise resting-state functional connectivity (rsFC) of the thalamic nucleus in drug-naïve patients with first-episode schizophrenia (FES) with AVHs. In addition, dynamic causal modeling was applied to compute effective connectivity and estimate causal relationships that could explain aberrant rsFC. Compared with the FES patients without AVH (NAVH) and normal controls, patients with AVHs had weaker rsFC of the bilateral medial pulvinar (PuM) nucleus-cerebellum. Moreover, compared with the normal control group, the AVH and NAVH groups had significantly stronger rsFC of the bilateral PuM nucleus-cerebral cortex, as well as weaker rsFC of the right medial geniculate nucleus-cerebral cortex. Compared with the NAVH and normal control groups, dynamic causal modeling revealed significantly stronger effective connectivity from the left PuM nucleus to the right inferior frontal gyrus in the AVH group. These findings indicate that the critical structure in the thalamus underlying AVHs is the PuM nucleus, and provide direct evidence that the cerebello-thalamo-cortical circuit is associated with AVHs.